1982
DOI: 10.1149/1.2123615
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Behavior of Gold‐Based Ohmic Contacts to the InP / InGaAsP Material System

Abstract: The performance and reliability of semiconductor devices depend critically on the electrical quality and stability of the metal contacts. Gold‐based metallizations are generally used to form ohmic contacts and Schottky barriers to the III–V material systems. In this paper, we study the interfacial reaction of Be‐Au and Sn‐Au ohmic contact metallizations on normalInP , normalInGaAsP , and normalInGaAs . Staining, cathodoluminescence imaging, and x‐ray microanalysis are used to analyze the metallurgical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Evolved gas analysis (EGA) experiments showed that gold-based metallizations deposited on the surface of InP greatly enhance the thermal decomposition of the semiconductor, the total quantity of evolved phosphorus being roughly proportional to the quantity of gold (Mojzes et al 1986). Moreover, a strong tendency of Au to migrate in depth into the InP substrate during the alloying of contacts was also reported; it was found that the diffusion depth of Au is directly proportional to the thickness of gold-based contact layer (Camlibel et al 1982). Thus, a substantial reduction in the amount of Au available for reaction with the surface of the semiconductor is necessary for optimization of the contact properties.…”
Section: Introductionmentioning
confidence: 99%
“…Evolved gas analysis (EGA) experiments showed that gold-based metallizations deposited on the surface of InP greatly enhance the thermal decomposition of the semiconductor, the total quantity of evolved phosphorus being roughly proportional to the quantity of gold (Mojzes et al 1986). Moreover, a strong tendency of Au to migrate in depth into the InP substrate during the alloying of contacts was also reported; it was found that the diffusion depth of Au is directly proportional to the thickness of gold-based contact layer (Camlibel et al 1982). Thus, a substantial reduction in the amount of Au available for reaction with the surface of the semiconductor is necessary for optimization of the contact properties.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain ohmic properties and low specific contact resistance values, such contacts must be alloyed at temperatures of about 400-425OC. However, during this heat treatment of contacts, a strong metallurgical interaction between the Au, In and P takes place at the contact-semiconductor interface, especially when goldbased metallizations are evaporated in thick layers (6,7). As a result, non-planar spiking reaction fronts are formed with a deep protrusion of Au into the semiconductor, which can cause a degradation of contacts and device reliability problems (7).…”
Section: General Approachmentioning
confidence: 99%